1985
DOI: 10.1001/jama.1985.03360070057023
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Exercise on Serum Lipid and Lipoprotein Levels Seen With Changes in Body Weight

Abstract: Ninety-five studies conducted between September 1955 and October 1983 measuring changes in human serum lipid and lipoprotein levels in response to exercise training were analyzed using meta-analysis. Change in body weight during exercise training may confound observed serum lipid and lipoprotein level changes; thus, data from these studies were partitioned into those where subjects gained body weight, maintained body weight, or lost body weight. Results showed differential changes in cholesterol, triglyceride,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
4
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(38 citation statements)
references
References 88 publications
2
30
4
2
Order By: Relevance
“…Exercise interventions rarely bring about reductions in LDL-C [37]; however, exercise training can increase lipoprotein lipase activity and, thus, improve HDL-C and triglyceride concentrations [37][38][39]. Fatness (waist girth, centimeters) and fitness (VO 2 max, milliliters per kilogram FFM per minute) were independently related to HDL-C and triglycerides in the present study, and the available evidence suggests that exercise training may improve HDL-C and triglyceride concentrations with or without weight loss [40][41][42]. The reported changes in HDL-C were modest, but the quality of most interventions was poor.…”
Section: Discussionmentioning
confidence: 49%
“…Exercise interventions rarely bring about reductions in LDL-C [37]; however, exercise training can increase lipoprotein lipase activity and, thus, improve HDL-C and triglyceride concentrations [37][38][39]. Fatness (waist girth, centimeters) and fitness (VO 2 max, milliliters per kilogram FFM per minute) were independently related to HDL-C and triglycerides in the present study, and the available evidence suggests that exercise training may improve HDL-C and triglyceride concentrations with or without weight loss [40][41][42]. The reported changes in HDL-C were modest, but the quality of most interventions was poor.…”
Section: Discussionmentioning
confidence: 49%
“…3 ± 7 On the other hand, reduction of body weight decreases the concentration of serum cholesterol and low-density lipoprotein (LDL) cholesterol. 8 Several studies support the hypothesis that oxidation of LDL promotes atherogenesis, 9 ± 11 and LDL oxidation is associated with the severity of coronary atheroschlerosis. 12 The oxidative modi®cation of LDL is assumed to occur extravascularly in the arterial intima.…”
Section: Introductionmentioning
confidence: 88%
“…There is much variability in the results of exercise/ lipid-lowering studies, at least in part because of the heterogeneity of the study methods, populations, exercise interventions, and the use of adjuvant interventions such as diet or pharmacological lipid-lowering agents. A meta-analysis 32 of 95 studies, most of which were not randomized controlled trials, concluded that exercise leads to a reduction of 6.3% in total cholesterol, 10.1% in LDL cholesterol, and 13.4% in cholesterol/HDL cholesterol and 5% increase in HDL cholesterol. It appears that the training intensities required to yield modest improvements in lipids are not as high as those that lead to improvements in fitness levels, as HDL appears to increase across a broad spectrum of exercise intensities.…”
Section: Lipidsmentioning
confidence: 99%